Indian corporate law - Herald Monis (Mangalore United Agencies, 2017)
The book is prepared as per the CBCS syllabus of Mangalore University. The contents of this book comprehensively cover the provisions of the Indian Companies Act, 2013 as amended from time to time. All the Possible attemps have been made to present this book in a students friendly manner.
Keywords: Corporate Law; Shares and Debentures; Company Management; Company Meetings; Formation of Company; VI SEM BCom